Role of hypoxic exosomes and the mechanisms of exosome release in the CNS under hypoxic conditions - Yang, Rong; Li, Zheng; Xu, Jing; Luo, Juan; Qu, Zhichuang; Chen, Xin; Yu, Sixun; Shu, Haifeng (Frontiers in Neurology, 2023)
Hypoxia is characterized by low oxygen levels in the body or environment, resulting in various physiological and pathological changes. The brain, which has the highest oxygen consumption of any organ, is particularly susceptible to hypoxic injury. Exposure to low-pressure hypoxic environments can cause irreversible brain damage. Hypoxia can occur in healthy individuals at high altitudes or in pathological conditions such as trauma, stroke, inflammation, and autoimmune and neurodegenerative diseases, leading to severe brain damage and impairments in cognitive, learning, and memory functions. Exosomes may play a role in the mechanisms of hypoxic injury and adaptation and are a current focus of research. Investigating changes in exosomes in the central nervous system under hypoxic conditions may aid in preventing secondary damage caused by hypoxia. This paper provides a brief overview of central nervous system injury resulting from hypoxia, and aimed to conduct a comprehensive literature review to assess the pathophysio-logical impact of exosomes on the central nervous system under hypoxic conditions.